2022
DOI: 10.1093/jole/lzac005
|View full text |Cite
|
Sign up to set email alerts
|

A Cognitive Bias for Zipfian Distributions? Uniform Distributions Become More Skewed via Cultural Transmission

Abstract: There is growing evidence that cognitive biases play a role in shaping language structure. Here, we ask whether such biases could contribute to the propensity of Zipfian word-frequency distributions in language, one of the striking commonalities between languages. Recent theoretical accounts and experimental findings suggest that such distributions provide a facilitative environment for word learning and segmentation. However, it remains unclear whether the advantage found in the laboratory reflects prior ling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…This skewness might have implications for learning, as suggested by recent studies showing improved learning in such distributions (e.g., Hendrickson & Perfors, 2019 ; Kurumada et al, 2013 ; Lavi-Rotbain & Arnon, 2020 , 2021 , 2022 ). This learnability advantage is also supported by findings showing that speakers turn uniform distributions into skewed ones in the process of cultural transmission, a pattern consistent with the presence of a cognitive bias for them (Shufaniya & Arnon, 2022 ). It has been shown that word segmentation is facilitated in language-like distributions.…”
Section: Discussionsupporting
confidence: 63%
“…This skewness might have implications for learning, as suggested by recent studies showing improved learning in such distributions (e.g., Hendrickson & Perfors, 2019 ; Kurumada et al, 2013 ; Lavi-Rotbain & Arnon, 2020 , 2021 , 2022 ). This learnability advantage is also supported by findings showing that speakers turn uniform distributions into skewed ones in the process of cultural transmission, a pattern consistent with the presence of a cognitive bias for them (Shufaniya & Arnon, 2022 ). It has been shown that word segmentation is facilitated in language-like distributions.…”
Section: Discussionsupporting
confidence: 63%
“…In Experiment 3, we test the effect of inductive biases in vocabulary distribution: does a bias towards a human-like Zipfian vocabulary distribution (Zipf, 1936) help language learning? Lan-guage is structured not only in how tokens relate, but also in the structure of the distribution that tokens are drawn from, a cognitive bias that is especially significant for memory-based theories of grammar (Shufaniya and Arnon, 2022;Piantadosi, 2014;Ellis and O'Donnell, 2012). We show that a Zipfian pretraining bias makes models better at downstream language learning even when there is no correspondence between the pretraining and fine-tuning vocabularies.…”
Section: Pretraining: Inject Structural Inductive Biasmentioning
confidence: 88%
“…We next investigate structural biases in the lexicon: how a cognitive bias towards vocabulary distributions (i.e., which tokens are more likely to appear in a corpus of language) affects learning. We aim to answer: does a bias towards a Zipfian vocabulary distribution (Shufaniya and Arnon, 2022;Piantadosi, 2014) act as a structural bias that aids language learning? A feature pervasive across human languages is the unbalanced nature of vocabulary distributions.…”
Section: Vocabulary Distributionmentioning
confidence: 99%
“…Skewed distributions have also been found to facilitate visual statistical learning (discovering recurring visual triplets in a continuous stream, 20 ); cross-situational word learning 21 ; and learning novel grammatical categories 22 and constructions 23 . Speakers seem to have a cognitive preference for such distributions: uniform distributions of made-up nouns become skewed when a story is transmitted from one participant to another 24 . Though there are relatively few studies that explore the impact of skew on learning, the ones that do, find that skew can be beneficial for learning a range of linguistic and non-linguistic relations.…”
Section: Introductionmentioning
confidence: 99%